Molecular characteristics of the structure protein VP1 in Coxsackievirus A10 Isolates from China - Hua Wang; Wenhong Wang; Guoqing Chen; Chuanjie Hu; Shengjie Chen; Lingxiang Mao; Hongxing Shen (Journal of Infection in Developing Countries)
Introduction: Coxsackievirus A10 (CVA10) is a non-enveloped, positive-sense single-stranded RNA virus classified within the Enterovirus genus in the Picornaviridae family. It is among the pathogens that can cause hand, foot and mouth disease. This study aimed to analyze the temporal and spatial distribution of CVA10 in China to understand its epidemiological characteristics of CVA10.